Antibacterial Potency of Pleurotus ostreatus Extract From Fruiting Body and its Solid Substrate on Staphyllococcus aureus - I. Badarina; D. Evvyernie; E. N. Herliyana; L. K. Darusman; T. Toharmat (Universitas Bengkulu, 2020)
The objective of this research was to evaluate the antibacterial potency of ethanol extract from fruiting body of Pleurotus ostreatus and Its solid substrate made from coffee husk and sawdust on the growth of Staphylococcus aureus ATCC 25922. The extract of Ganoderma lucidum fruiting body and Tetracycline antibiotic paper disk 30µg/disk were used as control. The samples were extracted by using maceration method in 30% ethanol solution. The extracts were diluted with sterile distilled water to concentration 500, 1000, and 5000ppm. The result showed that the ethanol extracts from fruiting body of Pleurotus ostreatus and Ganoderma lucidum and the extracts of coffee husk and sawdust substrate fermented by Pleurotus ostreatus could inhibit the growth of bacteria for all the concentration. There was a significant difference in diameter of cleared zones between Tetracycline antibiotic disc 30?g and the ethanol extracts of the samples (p<0.01). The diameter of cleared zones among the sample extracts and each dilution concentrations were not a significant difference (p>0.05). Tetracycline was sensitive to S.aureus ATCC25922, while all the extracts were resistant. This study confirmed that there were the antibacterial potency of mushroom extracts from the fruiting body and also its solid substrates.